BLOOD GLUCOSE TEST FOR DM TYPE 2 - Desi Oktariana; Gita Dwi Prasasty; Evi Lusiana; Nia Savitri Tamzil; Phey Liana; Kemas Ya’kub Rahadiyanto (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Indonesia is one of the countries with a high prevalence of diabetes, with total cases of diabetes in adults reaching 10 million cases, 6.2% of the total adult population. Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both. Insulin resistance in muscle and liver cells and pancreatic beta-cell failure has been recognized as the pathophysiology of major damage of type 2 diabetes. The blood glucose test is an important laboratory examination that can be used to diagnose, screen, and monitor DM type 2. There are several types of blood glucose levels, including random blood glucose tests, fasting blood glucose tests, post prandial blood glucose tests, oral Glucose Tolerance Test (OGTT), and HbA1c. Type 2 DM is often called the silent killer because sufferers are often late for self-examination and treatment so that complications arise early. Early symptoms of type 2 diabetes can be identified through blood sugar examination and risk factor screening. Screening for type 2 DM can detect abnormalities as early as possible so that interventions can start as early as possible to minimize the complication rate so that the quality of life can be maintained or better.